2020
DOI: 10.1155/2020/8235149
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Evaluation for Personalized Interventions in Children with Tuberculosis: Should It Be Routinely Performed?

Abstract: Childhood tuberculosis (TB) is a significant public health problem and the ninth leading cause of death worldwide. Progression of Mycobacterium tuberculosis infection to active disease depends on mycobacterial virulence, environmental diversity, and host susceptibility and immune response. In children, malnutrition and immaturity of the immune system contribute to an inadequate immune response. Coinfections, though rarely described in TB, might be associated with host immune deficiencies. Here, we describe the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
(38 reference statements)
0
3
0
2
Order By: Relevance
“…In addition, within the first year of life, infants do not have fully mature Toll-like receptors to allow for phagocytosis of the pathogen, so this could also impair children’s immune responses to mycobacterium [ 60 ]. In a study conducted by Carreto-Binaghi, it was found that some pediatric patients infected with tuberculosis had a lessened innate immune response due to low levels of IL-8, which prevented them from clearing the infection out of their system with their first line of defense [ 61 ]. A summary of immunodeficiencies in infants are shown in Figure 1 .…”
Section: Pediatric Immunology and Increased Susceptibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, within the first year of life, infants do not have fully mature Toll-like receptors to allow for phagocytosis of the pathogen, so this could also impair children’s immune responses to mycobacterium [ 60 ]. In a study conducted by Carreto-Binaghi, it was found that some pediatric patients infected with tuberculosis had a lessened innate immune response due to low levels of IL-8, which prevented them from clearing the infection out of their system with their first line of defense [ 61 ]. A summary of immunodeficiencies in infants are shown in Figure 1 .…”
Section: Pediatric Immunology and Increased Susceptibilitymentioning
confidence: 99%
“…As pediatric tuberculosis elicits different cytokines and T cells, as well as manifests in different organs, and has fewer mycobacteria in the system when compared to adults, this should be kept in mind when managing pediatric patients. Due to their immune system being weaker at eliciting the most beneficial innate host defense mechanisms, pediatric patients are more susceptible to Mtb and more detrimental prognoses [ 61 ].…”
Section: Pediatric Immunology and Increased Susceptibilitymentioning
confidence: 99%
“…В литературе описан феномен «иммунного паралича» у детей и новорожденных при сепсисе, вирусных инфекциях, травмах и асфиксии и во всех случаях оно было w w w . r e a n i m a 2 0 2 2 , 1 8 ; 6 Обзоры ассоциировано с высоким уровнем смертности [98][99][100]. К внешним и внутренним факторам, способствующим развитию этого феномена, относят наследственность, применение кортикостероидов, химиотерапии, иммуносупрессивной терапии [101,102].…”
Section: этиология и патогенез спон у новорожденныхunclassified
“…We recently proposed a simple method to assess the immune status of children that could provide information on whether a patient should receive immunotherapy together with their standard antituberculosis regime. 147 When immune profiles are available, it would be straightforward to determine whether a patient needs an immunostimulant, an immunosuppressor, or the supplementation of the absent immune effector.…”
Section: Immunomodulators Towards Personalized Tb Treatmentmentioning
confidence: 99%